1990
DOI: 10.1007/bf00043689
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of tobacco protoplasts with DNA entrapped in pH-sensitive liposomes

Abstract: A system for the transformation of tobacco mesophyll protoplasts using pH-sensitive liposomes was developed. Plasmid DNA (plGVneo23) encoding the NPT-II gene for kanamycin resistance was entrapped in pH-sensitive liposomes composed of dioleolphosphatidylethanolamine, cholesterol and oleic acid. These liposomes release their contents at low pH and are capable of delivering their contents into the cytoplasm of protoplasts. Kanamycin-resistant colonies were reproducibly recovered from transformed protoplasts at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Xanthi transformed with the plasmid pLGVneo23 containing pnos-npt H (nos promoter sequence and the npt II structural gene) (Zhu et al 1990). Npt II encodes kanamycin resistance.…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Xanthi transformed with the plasmid pLGVneo23 containing pnos-npt H (nos promoter sequence and the npt II structural gene) (Zhu et al 1990). Npt II encodes kanamycin resistance.…”
Section: Cell Linesmentioning
confidence: 99%
“…Preliminary tests indicated that the extraction buffer (Zhu et al 1990) interfered with the ELISA assay. Therefore, 0.25 M Tris buffer (pH 7.8) was used to extract protein from tissue for ELISA tests.…”
Section: Npt H Protein Estimation By Elisamentioning
confidence: 99%
See 1 more Smart Citation